Formas de relevo da bacia hidrográfica do Rio Ibicuí, Rio Grande do Sul, Brasil: Obtidas por classificação topográfica automatizada - Romario Trentin; Luís Eduardo de Souza Robaina (Confins)
Ratings automated, increasingly the use of tools for GIS geomorphological studies because streamline the processing of information and allows quantification of the results quickly with less subjectivity. This study aimed to establish the definition of landforms units, through Geomorphons elements generated from automated classification of topographic for the river Ibicuí basin, in the Western of Rio Grande do Sul State. For the preparation of work was used radar data from the SRTM, with spatial resolution of 90 meters. The generation of Geomorphos elements was done in a virtual environment on the site . By visual interpretation in GIS environment allowed the definition of 12 landforms units to the Ibicuí Basin, so called: Ibicuí-Uruguay Unit formed by large areas with a flat element; Flood Plain Unit characterized by the flat element associated with tributaries of the Ibicuí river; Altitude Hills Unit, with broad slopes and altitudes above 200m; Volcanic ridge Unit forming relief dissected with valleys and ridges; Sedimentary Edge Unit defined by shoulders and secondary elevations associated with relief of flat elements; Cacequi Unit formed by undulating relief marked by wide slopes and areas with hollow forms and short valleys; Santa Maria Unit of smooth wavy relief and isolated elevations; High Course of Ibirapuitã Unit, constituting the areas in the headwaters of the upper course of the Ibirapuitã and Ibirapuitã Chico rivers; Serra do Caverá Unit composed of a relief of hills and morrotes; Taquarembó Unit characterized by slopes with narrow and elongated tops with substrate composed of granite rocks; Santa Maria Chico Unit forming slopes with broad bases with rebounds of metamorphic and granite rock outcrops; Alegrete Unit with flat forms associated to bumps between the middle and top of the slope that mark outcrops of blocks and slabs.. The units distinguished differences of physiographic aspects that it can be observed in the field and has geomorphological representation.